Analisis Pengembangan Keprofesian, Sikap Kewirausahaan Dan Evaluasi Program Pendidikan Terhadap Pengembangan Kinerja Guru - Agustina Sri Purnami; M Mulyoto; S Sunarto; M Mulyanto (Universitas Sarjanawiyata Tamansiswa, 2020)
Thus this research was conducted as a basis for reviewing the MP Study Program curriculum. This research is to analyze the subject in the department to achieve the vision of the Educational Management Department which makes a positive and significant contribution to the graduate profile. Data analysis was tested with multiple linear regression, followed by partial correlation. The results obtained are the coefficient values between Professional Development, Program Evaluation, and Entrepreneurship Attitudes with Teacher Performance obtained values R = 0.784, with R2 = 0.597, with a value of F = 36.098 with a significance of 0.000. This means that there is a close relationship between the three independent variables, the dependent variable with R2 = 0.597 indicates that 59.7% of teacher performance is influenced by the three independent variables. Next is a partial correlation analysis. The results obtained are r1y-23 = 0.389 with a significance of 0.001, r2y-13 = 0.257 with a significance of 0.032, and r3y-12 = 0.324 with a significance of 0.006. From the results it was seen that the highest contribution was achieved by Professional Development, followed by the Entrepreneurship Attitude, the smallest; is the contribution of the Program Evaluation